3D printed carboxymethyl cellulose scaffolds for autologous growth factors delivery in wound healing. (15th February 2022) - Diaz-Gomez, Luis; Gonzalez-Prada, Iago; Millan, Rosendo; Da Silva-Candal, Andres; Bugallo-Casal, Ana; Campos, Francisco; Concheiro, Angel; Alvarez-Lorenzo, Carmen
Abstract: This work aims to use carboxymethyl cellulose (CMC) as main structural and functional component of 3D printed scaffolds for healing of diabetic wounds. Differently from previous inks involving small contents in CMC, herein sterile (steam-heated) concentrated CMC solely dispersions (10–20%w/v) were screened regarding printability and fidelity properties. CMC (15%w/v)-citric acid inks showed excellent self-healing rheological properties and stability during storage. CMC scaffolds loaded with platelet rich plasma (PRP) sustained the release of relevant growth factors. CMC scaffolds both with and without PRP promoted angiogenesis in ovo, stem cell migration in vitro, and wound healing in a diabetic model in vivo . Transparent CMC scaffolds allowed direct monitoring of bilateral full-thickness wounds created in rat dorsum. CMC scaffolds facilitated re-epithelialization, granulation, and angiogenesis in full-thickness skin defects, and the performance was improved when combined with PRP. Overall, CMC is pointed out as outstanding component of active dressings for diabetic wounds. Graphical abstract: Unlabelled Image